Prognostic Significance of B-Type Natriuretic Peptide in Patients With Left Ventricular Thrombus - An, Zhixia; Gao, Zhichun; Wang, Luyu; Hou, Changchun; Zhang, Liying; Gong, Siming; Rao, Rongsheng; Li, Chun; Qin, Zhexue (Frontiers in Cardiovascular Medicine, 2021)
Background and aims: There is sparse information on the prognostic value of B-type natriuretic peptide (BNP) for the outcomes in patients with left ventricular thrombus (LVT). Methods: Patients diagnosed with LVT by transthoracic echocardiography between November 2009 to July 2020 at our institution were included. The endpoints were all-cause mortality and systemic embolism. Results: Ninety-two subjects were finally included in the study. The mean age of the cohort was 56.73±14.12, and 80.4% of the patients were male. The median BNP (1st quartile- 3rd quartile) was 437.5 (112.74-1317.5). The total all-cause mortality rate was 30.44% (28/92), and the 1-year, 2-year and 3-year cumulative survival rates were 85.4%, 75.5% and 66.5% respectively. Systemic embolism was identified in 10 subjects. COX multivariate analysis showed that Log BNP (HR, 4.16; 95%CI, 1.81-9.56; P=0.001) and BMI (HR, 0.86; 95%CI, 0.73-0.99; P=0.048) were significantly associated with all-cause mortality. In addition, patients with BNP levels in the upper median (≥ 437.5pg/ml) had significantly higher all-cause mortality rate compared to those with lower median BNP (<437.5pg/ml; P=0.004). The area under the receiver operating characteristic curve for BNP and all-cause mortality was 0.71. In the linear trend test, BNP quartiles were significantly related to all-cause mortality in all models, and the P values for trend in models 1, 2 and 3 were 0.005, 0.006 and 0.048 respectively. Conclusion: BNP level is a prognostic factor for all-cause mortality in LVT patients, and elevated BNP is indicative of a higher risk of LVT.